Part Summary of the Project 'Speakers' Comfort': Teachers' Voice Use in Teaching Environments. Issue 3 (December 2015) - Lyberg-Åhlander, Viveka; Rydell, Roland; Löfqvist, Anders; Pelegrin-García, David; Brunskog, Jonas
Classroom acoustics not always take the speaker's comfort into consideration. The purpose of the presented papers was to investigate voice use, vocal behavior and prevalence of voice problems in Swedish teaching staff. Ratings of features in the work-environment on voice use were explored in n = 487 teachers. Based on their answers the respondents were split into two groups: teachers with self-assessed voice problems and voice-healthy teachers. Teachers with voice problems and were matched to a voice-healthy colleague from the same school and were investigated and compared for clinical findings and for vocal behavior. Acoustic properties of their teaching environments were measured. Teachers with voice-problems were more affected by any loading factor in the work-environment and were more aware of the room acoustics. Differences between the groups were found during field-measurements, while there were no differences in the findings from the clinical examinations of the larynx and voice. Voice problems seem to emerge in the interplay with and use of the classroom acoustics.